The building blocks of matter - Haynes, Delia A. (HTS teologiese studies, 2021)
The question of what everything around us is made from has fascinated humanity since ancient times. The development of ideas on what the building blocks of matter are, and how these building blocks come together to form materials, are discussed in this contribution. In order to manipulate matter in a useful way, an understanding of the structure of the building blocks is the key. For this reason, atomic theory and bonding theory are introduced. An explanation of the periodic table shows why it is such a powerful predictive tool, and the use of symbols in chemistry is discussed.Contribution: In this article, the historical development of key ideas in our understanding of matter is presented, along with some of the important ideas in understanding how matter behaves. As part of this special collection, the implications of the meaning and utilisation of this knowledge are also considered.